Regulating Water Services : Sending the Right Signals to Utilities in Chile - Bitrán, Gabriel; Arellano, Pamela (World Bank, Washington, DC, 2012)
During the 1980s and 1990s the Chilean water and sanitation sector underwent deep reforms so that private capital could finance the huge investments needed to achieve universal service. The regulatory framework put into place cleared the way for massive private equity. But users have also paid the price of transforming the heavily subsidized sector into a self-sustaining industry able to provide universal coverage. This Note examines key features of the new regulatory scheme that have contributed to the sustainability of the reforms: a phased approach, an efficient pricing policy and methodology, and expert panels to deal with conflict resolution.